Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1103/physrevlett.115.158101
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Mechanism for Biological Homochirality of Early Life Self-Replicators

Abstract: The observed single-handedness of biological amino acids and sugars has long been attributed to autocatalysis. However, the stability of homochiral states in deterministic autocatalytic systems relies on cross inhibition of the two chiral states, an unlikely scenario for early life self-replicators. Here, we present a theory for a stochastic individual-level model of autocatalysis due to early life selfreplicators. Without chiral inhibition, the racemic state is the global attractor of the deterministic dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 29 publications
0
108
0
Order By: Relevance
“…32 This is so because first, the total number of molecules is conserved by our reaction scheme, hence so is the total concentration n = a + d + l. Second, the total chiral matter χ = d + l is a fast degree of freedom relative to the enantiomeric excess θ. 33 Simulations of the fully reversible scheme Eqs.…”
Section: Appendix A: Probability Distribution For the Enantiomeric Exmentioning
confidence: 97%
See 2 more Smart Citations
“…32 This is so because first, the total number of molecules is conserved by our reaction scheme, hence so is the total concentration n = a + d + l. Second, the total chiral matter χ = d + l is a fast degree of freedom relative to the enantiomeric excess θ. 33 Simulations of the fully reversible scheme Eqs.…”
Section: Appendix A: Probability Distribution For the Enantiomeric Exmentioning
confidence: 97%
“…In this respect, Goldenfeld and co-workers recently reported that reaction noise in a closed model involving strictly irreversible enantioselective autocatalysis coupled with the uncatalyzed, reversible production of the enantiomers stabilizes the homochiral states, making these the most probable outcome of the system. 14 The purpose of this paper is to analyze in more detail the role of reaction noise in asymmetric autocatalytic reaction networks in the context of this proposal. In Sec.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, similar biochemical reactions to motif I have been studied in several biological contexts. 12,17,[33][34][35] The list of motifs provided herein should be helpful in searching for other candidates of biochemical reactions in which the small-number effect is expected to play an important role within a cell. Furthermore, considering recent advances in synthetic biology, [36][37][38] the list is also expected to be useful for designing a system that shows the small-number effect.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplicative noise naturally describes inhomogeneous diffusion in which fluctuations depend on the state of the system. Concrete applications are very diverse, covering a broad range of interest as, for instance, micromagnetism [10] and early life biology [11]. On the other hand, extended multiplicative systems present challenging phenomena, such as noiseinduced phase transitions (NIPT), stochastic resonance and pattern formation [12,13].…”
mentioning
confidence: 99%